2010
DOI: 10.1002/ptr.3187
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity‐guided isolation of antiproliferative compounds from Centaurea arenaria

Abstract: The antiproliferative effects of n‐hexane, chloroform and aqueous methanol extracts prepared from the whole plant of Centaurea arenaria M.B. ex Willd. were investigated against cervix adenocarcinoma (HeLa), breast adenocarcinoma (MCF7) and skin epidermoid carcinoma (A431) cells, using the MTT assay. The chloroform extract displayed high tumour cell proliferation inhibitory activity (higher than 85% at 10 μg/mL concentration), and was therefore subjected to a bioassay‐guided multistep separation procedure. Flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 23 publications
0
33
0
1
Order By: Relevance
“…Numerous effective anticancer drugs are either isolated from botanical sources or are modifications of natural molecules (Csapi et al, 2010;Al-Hazzani and Alshatwi, 2011;Hirchaud et al, 2013;Kitdamrongtham et al, 2013;Muthusami et al, 2013). Plants have received extensive attention as a source of potential antitumor agents in the past few decades and currently, most of the modern anticancer drugs such as camptothecin, vincristine, vinblastine, adriamycin, taxol, etoposide and paclitaxel are plant-derived compounds (Koppikas et al, 2010;Vidya Priyadarsini et al, 2010;Krifa et al, 2013).…”
Section: Natural Flavonoids As a Potential Source For Novel Chemothermentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous effective anticancer drugs are either isolated from botanical sources or are modifications of natural molecules (Csapi et al, 2010;Al-Hazzani and Alshatwi, 2011;Hirchaud et al, 2013;Kitdamrongtham et al, 2013;Muthusami et al, 2013). Plants have received extensive attention as a source of potential antitumor agents in the past few decades and currently, most of the modern anticancer drugs such as camptothecin, vincristine, vinblastine, adriamycin, taxol, etoposide and paclitaxel are plant-derived compounds (Koppikas et al, 2010;Vidya Priyadarsini et al, 2010;Krifa et al, 2013).…”
Section: Natural Flavonoids As a Potential Source For Novel Chemothermentioning
confidence: 99%
“…Plants have received extensive attention as a source of potential antitumor agents in the past few decades and currently, most of the modern anticancer drugs such as camptothecin, vincristine, vinblastine, adriamycin, taxol, etoposide and paclitaxel are plant-derived compounds (Koppikas et al, 2010;Vidya Priyadarsini et al, 2010;Krifa et al, 2013). Due to a significant untapped resource probably still remained in herbal medicines, it is crucial to keep up the search for plants with antitumor activity providing promising new leads for development of novel chemotherapeutics (Csapi et al, 2010;Al-Hazzani and Alshatwi, 2011;Ju et al, 2012;Meiyanto et al, 2012;Alonso-Castro et al, 2013).…”
Section: Natural Flavonoids As a Potential Source For Novel Chemothermentioning
confidence: 99%
“…lunensis Nowak et al (1984), Gousiadou and Skaltsa (2003) Centaurea araneosa Farrag et al (1993) Centaurea arenaria Nowak et al (1984), Gousiadou and Skaltsa (2003), Tešević et al (2007), Csapi et al (2010) Centaurea arenaria ssp. majorowii Nowak et al (1984), Gousiadou and Skaltsa (2003) Centaurea arenaria ssp.…”
Section: Centaurea Alexandrinamentioning
confidence: 99%
“…Cnicin (19) showed cytotoxic activity against KB with ED 50 = 3.4 lg/mL (Vanhaelen-Fastre, 1972), against TXL-5 mice lymphoma cells with ID 50 = 6 lg/mL (El-Marsy et al, 1984) and showed moderate antiproliferative effects against HeLa, and A431 human tumor cell lines (Csapi et al, 2010). The cytotoxic activities of some cnicin (19) and salonitenolide (4) derivatives were determined against A549 and MCF-7 tumor cell lines.…”
Section: Antitumor and Cytotoxicmentioning
confidence: 99%
“…In traditional medicine, C. species are used for fever, menstrual disorders, vaginal candidiasis, the treatment of liver, kidney and ulcer diseases, as antidiarrheal, stomachic, tonic, appetitive, antidiabetic, antipyretic, also as a diuretic and expectorant (6,7). Antiproliferative activity studies conducted on some Centaurea species in recent years have found that various extracts of these species significantly have antitumor activity (8)(9)(10)(11)(12)(13). In this study, the different extracts and fractions of active extract from aerial parts of C.kilaea were tested for antiproliferative activity against three human cancer cell lines (Hela; cervix adenocarcinoma, MCF-7; breast adenocarcinoma, PC-3; prostate adenocarcinoma) using MTT assay.…”
Section: Introductionmentioning
confidence: 99%